2015
DOI: 10.1016/j.psychres.2015.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive buying: Earlier illicit drug use, impulse buying, depression, and adult ADHD symptoms

Abstract: This longitudinal study examined the association between psychosocial antecedents, including illicit drug use, and adult compulsive buying (CB) across a 29-year time period from mean age 14 to mean age 43. Participants originally came from a community-based random sample of residents in two upstate New York counties. Multivariate linear regression analysis was used to study the relationship between the participant’s earlier psychosocial antecedents and adult CB in the fifth decade of life. The results of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 59 publications
2
27
1
Order By: Relevance
“…Second, future research should consider conducting longitudinal studies in order to gain some insight into the effects of mindsets in the development of compulsive buying behavior (Moschis, 2017). Previous research has shown that compulsive buying behavior usually develops over time and is often associated with childhood and adolescent experiences (Brook, Zhang, Brook, & Leukefeld, 2015; Grougiou et al, 2015). Similarly, mindsets are also shaped by external factors such as social networks and trusted people (Crum & Zuckerman, 2017).…”
Section: Limitations and Further Research Avenuesmentioning
confidence: 99%
“…Second, future research should consider conducting longitudinal studies in order to gain some insight into the effects of mindsets in the development of compulsive buying behavior (Moschis, 2017). Previous research has shown that compulsive buying behavior usually develops over time and is often associated with childhood and adolescent experiences (Brook, Zhang, Brook, & Leukefeld, 2015; Grougiou et al, 2015). Similarly, mindsets are also shaped by external factors such as social networks and trusted people (Crum & Zuckerman, 2017).…”
Section: Limitations and Further Research Avenuesmentioning
confidence: 99%
“…However, the rates of lifetime diagnosis of ADHD in compulsive buyers were found to be comparable to those of control subjects (4 % vs. 6 %, respectively) (Black et al 2012). Brook et al (2015) recently sought to determine the precursors of compulsive buying disorder across a 29-year time-period from mean ages 14 to 43 years. In this longitudinal study, earlier concurrent ADHD symptoms, as well as being female and having depression or illicit drug abuse were found to be independent precursors of compulsive buying disorder (Brook et al 2015).…”
Section: Compulsive Buying Disorder and Adhdmentioning
confidence: 99%
“…Brook et al (2015) recently sought to determine the precursors of compulsive buying disorder across a 29-year time-period from mean ages 14 to 43 years. In this longitudinal study, earlier concurrent ADHD symptoms, as well as being female and having depression or illicit drug abuse were found to be independent precursors of compulsive buying disorder (Brook et al 2015). It is apparent that the number of studies on the association of compulsive buying disorder with ADHD is not large enough to draw definitive conclusions, and that there is a need for further studies.…”
Section: Compulsive Buying Disorder and Adhdmentioning
confidence: 99%
“…Lastly, extant research has demonstrated gender differences in compulsive buying (Achtziger, Hubert, Kenning, Raab, & Reisch, 2015; Brook et al., 2015; d’Astous, 1990; Faber, Christenson, de Zwaan, & Mitchell, 1995; Koran, Bullock, Hartston, Elliott, & D’Andrea, 2002), as well as psychological symptoms, coping styles, and cognitive biases. Recent studies have also noted that the underlying factors of compulsive buying differ between males and females (e.g., see Mueller et al., 2011).…”
Section: Introductionmentioning
confidence: 99%